Perilaku Konsumsi Fashion Muslim di Era Digital Dalam Perspektif Islam (Studi Kasus Mahasiswa FEBI UIN Sumatera Utara) - Nasution, Siti Aminah; Sugianto, Sugianto; Nasution, Juliana (Jurnal Ilmiah Ekonomi Islam, 2024)
In Indonesia, Muslim fashion is increasingly important as an expression of religious identity and values, with consumers, particularly university students, utilizing technology to select products that comply with halal principles and Islamic ethics. This study aims to understand the influence of Muslim fashion consumption behavior in digital technology. This research methodology uses a quantitative approach with data collected through questionnaires with a sample of 100 active students at the Faculty of Economics and Islamic Business at UIN North Sumatra, then analyzed using simple linear regression with SPSS 22 software. The results show that Muslim fashion consumption behavior has a significant effect on technology utilization, with a t-count value of 9.056 and a p-value of 0.000, far below the 0.05 significance limit. The coefficient of determination (R-squared) of 0.456 indicates that 45.6% of the variation in technology utilization can be explained by Muslim fashion consumption behavior. This indicates that digital technology makes it easier for students to choose fashion products that are in accordance with Islamic values.